Dimensi Spiritual Keris Dalam Perspektif Filsafat Metafisika - Sembada, Andhika Djalu (CV. Kurnia Grup, 2025)
Keris is recognized as a cultural heritage that transcends material functions, believed to possess spiritual dimensions such as 'tuah' or 'power.' Existing literature tends to focus on cultural narratives, leaving a gap in the formulation of the ontological essence of the keris's spiritual phenomenon. This study aims to analyze and formulate the spiritual dimension of keris using the framework of Metaphysical Philosophy, especially Ontology and Hylomorphism, and to offer a philosophical interpretative model that can explain the interaction between the material and the spirituality of keris. This qualitative research uses the approach of Metaphysical Philosophy and Philosophical Hermeneutics, with primary data derived from the core concepts of Metaphysics and cultural/ethnographic texts. The main analytical techniques are conceptual-philosophical analysis and hermeneutic description. The research results show that the spiritual dimension of keris can be formulated ontologically. The novelty of this study lies in the proposed Spiritual Keris Hylomorphism Model, which defines the keris as a dual hylomorphic artifact. The 'blessing' of keris is interpreted as the actualization of potential (entelechy) and the Spiritual Form, which is transferred through Non-Physical Efficient Causality (the practices and austerities of the maker). These findings provide a profound theoretical basis for the spiritual aspects of the keris. The conclusion shows that the keris is an entity that manifests the interaction between Material Substance and Non-Physical Substance. This study contributes to the Philosophy of Culture by expanding the scope of Metaphysics to legitimize and analyze local spiritual phenomena.